Role of immunoglobulin E and mast cells in murine models of asthma - S.I. Mayr; R.I. Zuberi; F.-T. Liu (Brazilian Journal of Medical and Biological Research, 2003)
Immunoglobulin E (IgE) and mast cells are believed to play important roles in allergic inflammation. However, their contributions to the pathogenesis of human asthma have not been clearly established. Significant progress has been made recently in our understanding of airway inflammation and airway hyperresponsiveness through studies of murine models of asthma and genetically engineered mice. Some of the studies have provided significant insights into the role of IgE and mast cells in the allergic airway response. In these models mice are immunized systemically with soluble protein antigens and then receive an antigen challenge through the airways. Bronchoalveolar lavage fluid from mice with allergic airway inflammation contains significant amounts of IgE. The IgE can capture the antigen presented to the airways and the immune complexes so formed can augment allergic airway response in a high-affinity IgE receptor (FcepsilonRI)-dependent manner. Previously, there were conflicting reports regarding the role of mast cells in murine models of asthma, based on studies of mast cell-deficient mice. More recent studies have suggested that the extent to which mast cells contribute to murine models of asthma depends on the experimental conditions employed to generate the airway response. This conclusion was further supported by studies using FcepsilonRI-deficient mice. Therefore, IgE-dependent activation of mast cells plays an important role in the development of allergic airway inflammation and airway hyperresponsiveness in mice under specific conditions. The murine models used should be of value for testing inhibitors of IgE or mast cells for the development of therapeutic agents for human asthma.